USE OF CONTEXTUAL VOCABULARY TEACHING METHOD IN READING TEXTS OF TEACHING TURKISH AS FOREIGN LANGUAGE BOOKS - Mehmet ÜNAY (Fırat University, 2021)
Vocabulary teaching in teaching Turkish as foreign language is the most important one of the points to be considered carefully. The question of how to teach vocabulary is one of the main sources of this problem. There are lots of vocabulary teaching methods. Along with the traditional methods, new teaching techniques and methods are used today. Contextual vocabulary teaching method is a method that needs high-order thinking skills and that is used by lots of individuals consciously or unconsciously. The aim of this study is determining to what extend the reading passages of the books used in teaching Turkish as foreign language use contextual vocabulary teaching method. Document analysis was used as method in this study. In this direction, the reading texts of “Istanbul B1 and B2”, “Yeni Hitit B1 and B2” level teaching Turkish as foreign language books and the frequency of the use of contextual vocabulary teaching method in these reading texts were examined. In the analysis of data collection, topics of the books were categorized and according to the number of the use of the technique, frequencies and percentages were taken advantaged. The results of the study presented that, Yeni Hitit books have more reading passages and activities including contextual vocabulary teaching method. In addition, in terms of the number and qualification of the activities and examples, the books examined in the study are insufficient to use of contextual vocabulary teaching method while teaching vocabulary.